Spectroscopic and structural properties of bisphthalonitriles with O/S/SO2 grafting: Comparative theoretical and experimental studies - Ekineker, Gulcin; Pilet, Guillaume; Berber, Savas; Ahsen, Vefa; Dumoulin, Fabienne; Onal, Emel (Elsevier, 2016)
Three bisphthalonitriles with different grafting functions (O/S/SO2) have been selected for their future interest in the preparation of dimeric phthalocyanines with tailored properties. The bisphthalonitrile derivatives have been prepared and comparatively characterized. Their complete structural properties were investigated and their XRD-determined structures were compared with their DFT-optimized ones. Molecular orbital levels and energy gaps were also determined and analysed. The sulfonyl (SO2) function induces different behaviour compared to the S and O grafting which are more similar. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Bisphthalonitrile; Comparative characterization; Crystal structure; DFT calculations